2009
DOI: 10.1007/s10680-009-9185-y
|View full text |Cite
|
Sign up to set email alerts
|

Religious Socialisation and Fertility: Transition to Third Birth in The Netherlands

Abstract: Although previous studies have demonstrated that religious people in Europe have larger families, the role played by religious socialisation in the context of contemporary fertility behaviour has not yet been analysed in detail. This contribution specifically looks at the interrelation between religious socialisation and current religiosity and their impact on the transition to the third child for Dutch women. It is based on data of the first wave of the Netherlands Kinship Panel Study (2002)(2003)(2004) and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 61 publications
0
15
0
5
Order By: Relevance
“…A large literature has established a connection between religion and family behavior (e.g., Thornton, Axinn, and Hill 1992;Lehrer 2000;Teachman 2002;McQuillan 2004;Adsera 2006;Frejka and Westoff 2008;Berghammer 2009Berghammer , 2012. Various dimensions of religiosity, including attendance, commitment, and the centrality of religion in people"s lives, have been shown to be associated with many dimensions of family life such as marriage, divorce, and family size.…”
Section: Religion and Union Formation Choices: Three Potential Contexmentioning
confidence: 99%
See 1 more Smart Citation
“…A large literature has established a connection between religion and family behavior (e.g., Thornton, Axinn, and Hill 1992;Lehrer 2000;Teachman 2002;McQuillan 2004;Adsera 2006;Frejka and Westoff 2008;Berghammer 2009Berghammer , 2012. Various dimensions of religiosity, including attendance, commitment, and the centrality of religion in people"s lives, have been shown to be associated with many dimensions of family life such as marriage, divorce, and family size.…”
Section: Religion and Union Formation Choices: Three Potential Contexmentioning
confidence: 99%
“…Overall, macro and micro empirical research illustrate a correlation between family-related behaviors and religiosity (e.g., Tanfer 1987;Adsera 2006;Frejka and Westoff 2008;Philipov and Berghammer 2007;Berghammer 2009;Berghammer 2012). Studies that tested the relationship between religiosity and family patterns found a strong and positive association between religious affiliation and commitment, and conventional sexual values and behavior (e.g., in the U.S.: Thornton and Camburn 1987;Sweet and Bumpass 1990;Thornton, Axinn, and Hill 1992; in the Netherlands: Liefbroer and Gierveld 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, ethnicity and religiosity are also included in the control variables. It is expected that those of Roma ethnicity (Koycheva and Philipov, 2008) and those with religious beliefs will have a notably higher chance of a third child (Berghammer, 2009).…”
Section: Control Variablesmentioning
confidence: 99%
“…Historically, the Dutch population consisted primarily of Christians who were geographically divided, with Protestants in the north and Catholics in the south, and with very limited intermarriage. In churches and religious schools, pro-natalist and pro-family Christian teaching was prevalent (Berghammer 2009). Regular social meetings and strong social networks among church members provided both instrumental and emotional support to parents raising children.…”
Section: Religion: Secularization Of Dutch Societymentioning
confidence: 99%
“…Beginning in the mid-1960s, the Netherlands has become a highly secularized, non-religious nation (Need and de Graaf 1996), with around 40 % of the population not affiliated to any religion-one of the highest proportions in Europe (Statistics Netherlands 2007, p. 116). There has also been a sharp drop in church attendance, even among those who claim a religious affiliation (Berghammer 2009;De Graaf and Te Grotenhuis 2008). Religion has largely lost prominence in daily life and is rarely used today as a reference for behavior (see De Graaf and Te Grotenhuis 2008).…”
Section: Religion: Secularization Of Dutch Societymentioning
confidence: 99%